A description of reverse osmosis using practical Kedem-Katchalsky equations - Kargol, A (Kluwer Academic Publ, 1997)
The work is concerned with an analytical description of reverse osmosis using the Kedem-Katchalsky equations. The process has been considered for well-mixed solutions. We have obtained formulas describing the concentration of a solution (purified by reverse osmosis) as st function of the transport: parameters of a membrane, concentration of the initial solution, and the mechanical pressures on the membrane. The formulae are illustrated by numerical computations. Our results may be applicable to biophysical studies concerning reverse osmosis in biological membrane systems.
Keywords: membrane; solution; transport; reverse osmosis; transport equations